Evaluation of Laser Confocal Raman Spectroscopy as a Non-Invasive Method for Detecting Sperm DNA Contents - Li, Mengge; Ji, Yaxing; Wang, Dongmei; Zhang, Yanliang; Zhang, Huan; Tang, Yi; Lin, Ge; Hu, Liang (Frontiers in Physiology, 2022)
Research question: Is Raman spectroscopy an efficient and accurate method to detect sperm chromosome balance state by DNA content differences? Design: Semen samples were provided by diploid healthy men, and the analysis parameters met the current World Health Organization (WHO, 2010) standards. The DNA content was assessed by analysis of the corresponding spectra obtained from a laser confocal Raman spectroscope. The sperm sex chromosome information was obtained by fluorescence in situ hybridization (FISH). Comparative analysis were performed between FISH results and Raman spectral analysis results. Results: Different parts of the sperm head showed different spectral signal intensities, which indicated that there were different chemical components. Standard principal component analysis (PCA) can preliminarily classify sperm with different DNA contents into two groups. Further analysis showed that there were significant differences in the 785 DNA backbone peaks and 714-1162 cm-1 DNA skeleton regions among sperm with different DNA contents. The peak and regional peak of the DNA skeleton of X sperm were significantly higher than those of Y sperm (X vs Y, P < 0.05). The above sperm types were confirmed by FISH. ROC curve analysis shows that there is a correlation between the Raman spectrum data and FISH results. Conclusions: Raman spectroscopy can identify X and Y sperms by analyzing the DNA content difference. However, the accuracy of the detection still needs to be improved. Nevertheless, Raman spectroscopy has a potential application value in the field of sperm aneuploidy detection and may even be used as a non-invasive predictor of sperm aneuploid state in preimplantation genetic testing (PGT-A).